2020
DOI: 10.1109/tnsre.2020.3018786
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness-Optimized Ankle-Foot Orthoses Improve Walking Energy Cost Compared to Conventional Orthoses in Neuromuscular Disorders: A Prospective Uncontrolled Intervention Study

Abstract: In persons with calf muscle weakness, walking energy cost is commonly increased due to persistent knee flexion and a diminished push-off. Provided ankle-foot orthoses (AFOs) usually lower walking energy cost. To maximize the reduction in energy cost, AFO bending stiffness should be individually optimized, but this is not common practice. Therefore, we aimed to evaluate whether individually stiffnessoptimized AFOs reduce walking energy cost compared to conventional AFOs in persons with non-spastic calf muscle w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…If the ankle angle is successfully restricted, the ground reaction force can move further forward over the foot and in front of the ankle and knee [ 3 , 6 ]. This reduces quadriceps activation, and, subsequently, walking energy cost [ 7 , 8 ]. Additionally, DLS-AFOs can support the ankle power by storing energy when moving into dorsiflexion during the stance phase and releasing this energy during push-off, which also reduces walking energy cost [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…If the ankle angle is successfully restricted, the ground reaction force can move further forward over the foot and in front of the ankle and knee [ 3 , 6 ]. This reduces quadriceps activation, and, subsequently, walking energy cost [ 7 , 8 ]. Additionally, DLS-AFOs can support the ankle power by storing energy when moving into dorsiflexion during the stance phase and releasing this energy during push-off, which also reduces walking energy cost [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing the trade-off between normalizing the ankle angle and preserving ankle power has been shown to maximize the reduction in energy cost [ 5 , 6 , 11 ]. Considering this trade-off is patient-dependent [ 5 , 6 , 11 ], it is necessary to individualize the DLS-AFO stiffness [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each paper, when present, it is reported the AFO type(s), the customization criteria, the materials, the functional data/parameters, and the main outcome. Comfort assessment or other subjective scores are also reported Authors/year Population (size) AFO type/ customization criteria Material Motor tasks Functional parameters Other scores Main outcome Waterval et al 2021 [ 56 ] unilateral plantar flexor weakness (9) dorsal leaf spring AFO Spring leaf Stiffness customizable energy cost optimized (Ankle7, OttoBock) carbon fiber walking spatio-temporal parameters GRFs hip, knee, ankle kinematics and kinetics peak vertical GRF of the contralateral leg significantly reduced and symmetry improved (AFO vs. no AFO) Waterval et al 2021 & 2020 [ 32 , 33 ] calf muscle weakness (34) dorsal leaf spring AFO Spring leaf Stiffness customizable (Ankle7, OttoBock)e carbon fiber walking spatio-temporal parameters hip, knee, ankle kinematics and kinetics energy cost reduction in energy cost (AFO optimized stiffness vs. non optimized) Kerkum et al 2021 [ 35 ] healthy subjects (12) dorsal leaf spring AFO Spring leaf Stiffness customizable (Ankle7, OttoBock) carbon fiber walking Ankle-foot kinematics work and power Total ankle-foot power increase with increasing footplate stiffness Lin et al 2021 [ 57 ] post-stroke drop-foot (12) 1. energy-Storage 3D Printed AFO 2. anterior-support AFO PLA + nylon+titanium thermoplastic walking spatio-temporal parameters pelvis, hip, knee, ankle kinematics (sagittal plane) Evaluation of satisfaction (QUEST) increased gait velocity and stride length (AFO1 vs. AFO2; AFO1 vs. barefoot) improved satisfaction (AFO1) Meng et al 2021 [ 58 ] post-stroke drop-foot (15) morphology PA2200 Somos NeXt PA12 NA NA …”
Section: Resultsmentioning
confidence: 99%
“…A systematic review showed that AFO stiffness mainly affected ankle kinematics, suggesting that greater stiffness could generally result in a decreased peak ankle joint angle in both plantar flexion and dorsiflexion [5]. Some AFOs have been developed to assist insufficient muscle activity through resistance [6,7]. Therefore, it is necessary to know the effect of different kinds of AFOs with different moments of resistance on the gait of patients.…”
Section: Introductionmentioning
confidence: 99%